Resistensi Warga di Bantaran Ciliwung terhadap Rencana Penggusuran oleh Pemerintah - Pramudita Pramudita; Budhi Gunawan; Selly Riawanty (Universitas Negeri Medan, 2020)
This paper focuses on the topic of normalization which apparently is not always acceptable to the community, it raises resistance to the community. In this study entitled